Interleukin-10-Producing DC-10 Is a Unique Tool to Promote Tolerance Via Antigen-Specific T Regulatory Type 1 Cells - Comi, Michela; Amodio, Giada; Gregori, Silvia (Frontiers in Immunology, 2018)
The prominent role of tolerogenic dendritic cells (tolDCs) in promoting immune tolerance and the development of efficient methods to generate clinical grade products allow the application of tolDCs as cell-based approach to dampen antigen-(Ag) specific T cell responses in autoimmunity and transplantation. Interleukin (IL)-10 potently modulates the differentiation and functions of myeloid cells. Our group contributed to the identification of IL-10 as key factor in inducing a subset of human tolDCs, named DC-10, endowed with the ability of spontaneously release IL-10 and induce Ag-specific T regulatory type 1 (Tr1) cells. We will provide an overview on the role of IL-10 in modulating myeloid cells and in promoting DC-10. Moreover, we will discuss the clinical application of DC-10 as inducers of Ag-specific Tr1 cells for tailoring Tr1-based cell therapy, and as cell product for promoting and restoring tolerance in T-cell-mediated diseases.